Wkład kardynała Karola Wojtyły w dzieło I Synodu Biskupów w 1967 r. - Dyduch, Jan (Prawo Kanoniczne, 1996)
The Synod of Bishops was summoned shortly after the Second Vatican Council ended. This new institution in the Church was inspired by the Second Vatican Council’s teaching on collegiality in the Church. As a consequence of the Council Fathers’ postulates, Pope Paul VI established the Synod of Bishops by his motu proprio „Apostolica Sollicitudo”, dated 15 September 1965. The first Synod of Bishops was occupied with affairs that concerned the entire Church, i.e.: the teaching of the faith and its impediments, renewal of the code of Cannon Law, seminary formation of the candidates for the priesthood, mixed marriages and the renewal of the liturgy. Cardinal Karol Wojtyła, Archbishop of Cracow, was summoned to take part in the first Synod. Because of political restrictions, he could not directly participate in it. However, this did not prevent his being deeply engeged in the Synod. He carefully studied the synodal questions and elaborated them. He sent his opinion on all the above mentioned problems to the assembly of Bishops for discussion. Many of Archbishop K. Wojtyła’s statements and suggestions were employed in the Postsynodal Documents.